The effect of multiple vitrectomies and its indications on intraocular pressure - Hrvoje Kovacic (BMC Ophthalmology, 2019)
Abstract Background To assess the relationship between different indications for trans pars plana vitrectomies (PPV’s) and the intraocular pressure (IOP), and the effect of multiple PPV’s on the IOP. We also examined whether there were differences in the number of IOP-lowering medications or surgeries before and after PPV. Methods A retrospective study including all patients that underwent at least one PPV in the period from 2001 till 2014 at our clinic. Medical records of all patients were reviewed and clinically relevant data were entered in a database. Generalized estimating equations models for repeated measurements were used to examine the effect of the number of PPV’s on the IOP and on the risk of undergoing glaucoma surgery, for each of the indications for PPV. Results Of 1072 PPV’s 447 eyes fulfilled the inclusion criteria. The IOP increased with 3.0 mmHg after a PPV with indication retinal detachment (p < 0.001), but remained stable after PPV for epiretinal membrane (p = 0.555), macular hole (p = 0.695), and vitreous hemorrhage (p = 0.787). At the end of the follow-up period the number of IOP-lowering medications was significantly higher compared to baseline, except in the macular hole group (p = 0.103). Also, the number of eyes that underwent glaucoma surgery was significantly higher compared to the fellow (not-operated) eyes (p < 0.001). There was a significant association between the number of PPV’s and the final IOP for the indication retinal detachment (p = 0.009), and between the number of PPV’s and glaucoma surgery (odds ratio [95% confidence interval]: 2.60 [1.62–4.15]). Conclusions The IOP rises significantly after PPV with indication retinal detachment. This association was not found for other indications for PPV. Also, the risk of IOP-lowering surgeries was higher after PPV, but not different between the PPV indications. The IOP should be monitored carefully after PPV, since there may be a higher risk of secondary glaucoma.